2019
DOI: 10.1136/bmjopen-2019-031564
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to heavy physical work from early to later adulthood and primary healthcare visits due to musculoskeletal diseases in midlife: a register linked study

Abstract: ObjectivesTo examine whether exposure to heavy physical work from early to later adulthood is associated with primary healthcare visits due to cause-specific musculoskeletal diseases in midlife.DesignProspective cohort study.SettingNationally representative Young Finns Study cohort, Finland.Participants1056 participants of the Young Finns Study cohort.Exposure measurePhysical work exposure was surveyed in early (18–24 years old, 1986 or 1989) and later adulthood (2007 and 2011), and it was categorised as: ‘no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This explanation is supported by our observation that technicians-who are exposed to combination of all above mentioned ergonomic factors more frequently and intensively (Velasco Garrido et al 2018a)reported musculoskeletal pain more frequently than other offshore occupations. Besides the ergonomic factors discussed above, the incidence of musculoskeletal disorders (as shown by increased primary healthcare visits related to such problems) has also been associated with long term exposure to heavy physical work in general (Halonen et al 2019). In a field study assessing cardiopulmonary parameters during preparatory trainings for offshore work, working in such installations has been demonstrated to imply heavy physical work (Preisser Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation is supported by our observation that technicians-who are exposed to combination of all above mentioned ergonomic factors more frequently and intensively (Velasco Garrido et al 2018a)reported musculoskeletal pain more frequently than other offshore occupations. Besides the ergonomic factors discussed above, the incidence of musculoskeletal disorders (as shown by increased primary healthcare visits related to such problems) has also been associated with long term exposure to heavy physical work in general (Halonen et al 2019). In a field study assessing cardiopulmonary parameters during preparatory trainings for offshore work, working in such installations has been demonstrated to imply heavy physical work (Preisser Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the ergonomic factors discussed above, the incidence of musculoskeletal disorders (as shown by increased primary healthcare visits related to such problems) has also been associated with long term exposure to heavy physical work in general (Halonen et al 2019 ). In a field study assessing cardiopulmonary parameters during preparatory trainings for offshore work, working in such installations has been demonstrated to imply heavy physical work (Preisser et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yue et al [14] stated that preventing MSDs requires effective prevention strategies, which can be addressed in terms of individual, ergonomic and occupational factors. For instance, it is important to coach workers on how to recover from heavy work tasks using some recovery exercises [16]. Regular physical activities, such as yoga and cycling, can ease the pain and have a positive impact on musculoskeletal health [17].…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…The researcher classified the number of correct answers, which were linked to their level of knowledge of occupational health issues. More than 25 correct answers were classified as "Very Good", "Good" (21)(22)(23)(24)(25), "Relatively Good" (16)(17)(18)(19)(20), "Not Good" (10)(11)(12)(13)(14)(15) and "Poor" (less than 10).…”
Section: Key Findings (Related To the First Research Question)mentioning
confidence: 99%
“…Much of the current related literature addresses specific occupational areas. These include nursing, health service workers [8] and hard physical work [5,[11][12][13]. In this study we explore back disorders across a wide range of occupational categories.…”
Section: Introductionmentioning
confidence: 99%